The relationship between dietary calcium intakes contain in goats feed with calcium serum concentration in pregnant boer goats - Mohd Yusoff, Husna Fasihah; Abu Bakar @ Zakaria, Md Zuki; Abdullah, Faez Firdaus Jesse; Zainal Abidin, Siti Aimi Sarah (Textroad Publishing Corporation, 2016)
The aim of this research is to identify the relationship present between calcium concentrations in goats’ feed with calcium serum level for pregnant meat goat. The calcium was tested from both samples. There were between feed and blood serum. The biochemical parameters were studied using 40 pregnant does (10 animals in each group). The present study indicates those hematological calcium deficiencies are likely to happen due to low level of calcium concentration content in feed.